The subject of attention. - Jennings, Carolyn (Synthese, 2012)
The absence of a common understanding of attention plagues current research on the topic. Combining the findings from three domains of research on attention, this paper presents a univocal account that fits normal use of the term as well as its many associated phenomena: attention is a process of mental selection that is within the control of the subject. The role of the subject is often excluded from naturalized accounts, but this paper will be an exception to that rule. The paper aims to show how we might reinstate the subject into the act of attention, endorsing the ordinary notion that attention is a direction of the mind by the subject, rather than a mere occurrence or happening. To do so, it lays out the best work of phenomenology, psychology, and neuroscience on specifying the ordinary notion of attention and, in finding them individually wanting, combines them into a unified view that avoids the problems of each. In this way the paper presents a 'how possible' account of the ordinary notion of attention, wherein attention is enacted by a subject.